Mixed finite element approximation for a contact problem in electro-elasticity - TEDJANI HADJ AMMAR; BENYATTOU BENABDERRAHMANE; SALAH DRABLA (Kuwait Journal of Science, 2015)
The present paper is concerned with the frictionless contact problem between two electroelasticbodies in a bidimensional context. We consider a mixed formulation in which theunknowns are the displacement field, the electric potential field and the contact pressure. Weuse the mixed finite element method to approximate the solutions. Error estimates are derivedon the approximative solutions from which the convergence of the algorithm is deduced undersuitable regularity conditions on the exact solution.